Diptera Collectionis P. Gabriel Strobl - VIII (Verzeichnis der Dipteren-Arten der Kollektion Strobl). - Morge, Günter (Contributions to Entomology = Beiträge zur Entomologie, 1976)
Part VIII of the reports on the revision of P. Gabriel Strobl's collection of Diptera gives a survey of the species and genera of the collection. The preface describes the datail of it and also those of two handwritten special catalogues of Strobl as base of this survey.